IDDF2018-ABS-0053 Clinical significance of seprase in gastric cancer and its prognostic value on apatinib. (June 2018) - Hua, Yunqi; Yin, Fangrui; Yang, Yongyan; Liu, Xianfeng; Zhao, Cuiyun; Jin, Yunjian; Zhang, Wenhui; Li, Min; Zhao, Meili; Jin, Na
Abstract : Background: Apatinib, a novel inhibitor of VEGFR-2, has achieved survival improvement in advanced gastric cancer patients as the third-line treatment medicine. But lacking effective prognostic indicators, we investigated the expression of Seprase protein in gastric cancer and its prognostic value on apatinib. Methods: We conducted a retrospective study using data on 45 apatinib-treated advanced gastric cancer (GC), and 15 cases of normal gastric tissue >5 cm from the tumour was selected as control group. The immunohistochemical method was used to detect the expression of Seprase in two group, the relationship between Seprase expression and the clinicopathologic characteristics was studied. 45 GC patients were divided into two groups: seprase-negative and seprase-positive group. All the patients were orally given apatinib at a dose of 500 mg/day, and its prognostic significance and clinical efficacy on apatinib were statistically analysed. Results: The positive rate of seprase in GC was 71.11% (32/45) higher than that in normal tissue 20.00% (3/15) and with statistical significance (χ 2 =6.67, p=0.01); Seprase was related to the degree of differentiation (χ 2 =6.72, p=0.035) and lymphatic metastasis (χ 2 =4.874, p=0.027) of gastric cancer. Efficacy evaluation of apatinib in GC showed that the disease control rate (DCR) was 46.87% in seprase-positive group and 15.38% in seprase-negative group (p<0.05). As shown in table 1. The median progression-free survival (PFS) of two groups was 5.1 months and 3.0 months (p<0.05). Conclusions: Seprase play important roles in the invasion and metastasis of gastric cancer, apatinib make clinical benefit to Seprase-positive gastric cancer patients and thus provide a new direction for target therapy.